Existenzielle Soziale Arbeit - Nathschläger, Johannes (Verlag Julius Klinkhardt, 2023)
Social work meets existential philosophy: How do I find meaning in my life? How free am I in my decisions and actions? How do I deal with suffering, guilt and death? How do I lead an authentic life? Drawing on some great thinkers such as Jean-Paul Sartre and Martin Heidegger, Johannes Nathschläger attempts to show how existential philosophy questions and issues represent an omnipresent ""cross-sectional task"" in the diverse fields of action of social work, but have so far received little attention in theoretical discourse. Social work as a profession and scientific discipline must finally face this challenge and develop and apply appropriate methods. It can find inspiration in Irvin Yalom's existential psychotherapy or Viktor Frankl's logotherapy, among others. This book would like to initiate a debate on this and is aimed equally at professionals, students and teachers of social work.